2020
DOI: 10.1111/jfpp.14485
|View full text |Cite
|
Sign up to set email alerts
|

Optimization in the extraction of polyphenolic compounds and antioxidant activity from Opuntia ficus‐indica using response surface methodology

Abstract: The aim of this study was to find the optimal conditions for the extraction of phenolic compounds as well as antioxidant activities from Opuntia ficus‐indica via the response surface methodology using a maceration extraction technique. A Box–Behnken 33 design was used to optimize the process variables (ethanol concentration: 70%, 83%, and 96%; temperature: 24, 50, and 76°C; time: 30, 75, and 120 min) in the extraction of phenolic compounds, and the DPPH• and ABTS•+ antioxidant activities. The Statgraphics Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Results showed that E2 got the highest flavonoid content, indicating that extension of the maceration time of E2 extract allowed to increase its flavonoid content. Our findings are in convenience with those of Tranquilino-Rodríguez et al (2020). These authors reported that flavonoid contents of 70, 83 and 96% ethanolic extracts of young cladodes of Opuntia ficus-indica were ranged from 3.095 to 10.392 mg QE/g dw proportionally with the increase of EtOH concentration and extraction time from 30 to 120 min.…”
Section: Flavonoidsupporting
confidence: 89%
“…Results showed that E2 got the highest flavonoid content, indicating that extension of the maceration time of E2 extract allowed to increase its flavonoid content. Our findings are in convenience with those of Tranquilino-Rodríguez et al (2020). These authors reported that flavonoid contents of 70, 83 and 96% ethanolic extracts of young cladodes of Opuntia ficus-indica were ranged from 3.095 to 10.392 mg QE/g dw proportionally with the increase of EtOH concentration and extraction time from 30 to 120 min.…”
Section: Flavonoidsupporting
confidence: 89%
“…The experiments were established based on a Box–Behnken Design with the three factors of CN, CMC, and LBG at three levels of 0‒0.5%, 0‒0.15%, and 0‒0.15%, respectively (Table 1). The complete design included 17 experiments with five replicates at the center point to estimate the experimental error (Tranquilino‐Rodríguez, Martínez‐Flores, Rodiles‐López, Dios Figueroa‐Cárdenas, & Pérez‐Sánchez, 2020). The behavior of the system is expressed by the following generalized response surface model:Y=βO+false∑i=13βiXi+false∑i=13βitaliciiXi2+false∑i=13false∑j=i+13βiXiXj+ε…”
Section: Methodsmentioning
confidence: 99%
“…The complete design included 17 experiments with five replicates at the center point to estimate the experimental error (Tranquilino-Rodríguez, Martínez-Flores, Rodiles-López, Dios Figueroa-Cárdenas, & Pérez-Sánchez, 2020). The behavior of the system is expressed by the following generalized response surface model:…”
Section: Experimental Designmentioning
confidence: 99%